2020
DOI: 10.1155/2020/8897709
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experiences of Adolescent Mothers Attending Mbale Regional Referral Hospital: A Phenomenological Study

Abstract: Background. Adolescence is a period of transition from childhood to adulthood, and is a critical stage in ones’ development. It is characterized by immense opportunities and risks. By 2016, 16% of the world’s population was of adolescents, with 82% residing in developing countries. About 12 million births were in 15–19 year olds. Sub-Saharan Africa, particularly East Africa, has high adolescent pregnancy rates, as high as 35.8% in eastern Uganda. Maternal mortality ratio (MMR) attributable to 15–19 years olds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
0
13
0
2
Order By: Relevance
“…Author details 1 Faculty of Computer Sciences, Multimedia and Telecommunication, Universitat Oberta de Catalunya, Barcelona, Spain. 2 Consulting in Health Informatics, P.O Box 3966, Nairobi 00100, Kenya.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Author details 1 Faculty of Computer Sciences, Multimedia and Telecommunication, Universitat Oberta de Catalunya, Barcelona, Spain. 2 Consulting in Health Informatics, P.O Box 3966, Nairobi 00100, Kenya.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Adolescent pregnancies continue to negatively impact girls across the globe, with around 12 million girls aged 15 – 19 years giving birth annually in the developing world [ 1 ]. Information on sexual reproductive health [ 2 ] and contraception is lacking in majority of resource-limited settings [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This feeling of unpreparedness can lead to feelings of overwhelm and other negative mental health consequences ( 18 ). Additionally, when mothers are not connected with sufficient and appropriate support in the postpartum period, this can confer multiple negative side effects on mother and baby, including negative maternal emotional responses such as anxiety, stress, and loneliness ( 19 ). Maternal distress in turn is associated with impairments in maternal-infant interactions and caregiving practices ( 20 ), as well as impaired outcomes for the infant such as psychopathology and developmental issues ( 21 , 22 ).…”
Section: Importance Of Patient-centered Care To Postpartum Mental Healthmentioning
confidence: 99%
“…Other studies have reported that teenagers and their babies are prone to illness due to their ill-preparedness for the challenges of motherhood, gaps in health information, and lack of support [ 10 , 11 ]. Although the barriers to accessing maternity care among this population have been studied, there are few published studies that have explored the health care needs of the first-time teenage mothers during the postpartum period and how these can be met to reduce complications during this time period [ 6 , 10 , 12 ]. The current country postpartum care guidelines [ 13 ] are silent on the special care for teenage mothers although there is a need for healthcare workers to understand and integrate the health care needs for teenage mothers in their daily practice so as to improve client satisfaction, reduce complications and possibly increase the number of teenagers delivering at the health facilities.…”
Section: Introductionmentioning
confidence: 99%